Cultural governance in sustainable cities - Duxbury, Nancy (2014)
The paper proposes a three-part system of cultural governance for sustainable cities: culturally sensitive sustainability governance processes and structures, a cultural lens on all public policies/decisions and a sustainability approach to cultural policy/planning and governance.